'Families of mankind': British liberty, League internationalism, and the traffic in women and children. Issue 5 (3rd July 2020) - Morefield, Jeanne
ABSTRACT: The League of Nations' long term interest in the traffic in women and children mirrored, in key ways, what I call the 'familial internationalism' of some of its most influential British founders. Grounded in their understanding of the British Empire as an institution uniquely able to reconcile 'liberty and self-government' with the denial of liberty and self-government to the colonies, this vision of internationalism recast nations as cultural 'families of mankind' rather than political units with a right to sovereignty. This article thus explores first the influence of British imperial thought on League internationalism and then moves on to an analysis of the League's Advisory Committee on the Traffic in Women and Children. In contrast to most historical investigations of the Committee, I read these archives as multivocal sites of political and cultural contestation about the status of women in relation to the national 'family'. Ultimately, I argue, the work of the Committee resulted in an international convention that restricted women's liberty by making it more difficult for them to travel internationally.